Implementing an integrated family approach in mental health care for families experiencing complex and multiple problems: a case example in Amsterdam - Zegwaard, Agnes H.; Koop, Frederieke J.; Beuk, Nico; Broeks, Carlinde W.; Van, Rien L.; Konijn, Carolien; Franken, Aart; Middeldorp, Christel M.; Hein, Irma M. (Frontiers in Psychiatry, 2024)
For youth care professionals who work with families with complex needs, we implemented an interagency, family-focused approach involving child and adult mental health care services and child protection services. The primary objective of the collaboration was to minimize fragmentation in service delivery and to improve practitioners’ self-efficacy in supporting families. A total of 50 families were enrolled between 2020 and 2023. Quantitative descriptive analysis was conducted to map the sample characteristics and the correlations between the practitioners’ consultation requests and the recommendations they received. We evaluated the applicability of the model using semi-structured interviews. Results revealed the frequent socioeconomic and psychosocial challenges and co-current mental health issues faced by the families. As expected, practitioners who work with families experiencing complex and multiple problems encountered a range of difficulties in their service delivery. These related to barriers such as poor role demarcation between organizations, practitioners’ unrealistic expectations of other services, the impact of multiple problems on family well-being, and complicated family dynamics. The interprofessional collaboration improved the practitioners’ self-efficacy in supporting families. They also perceived improvements in child safety. The study emphasizes the need for clear pathways for youth care practitioners to obtain assistance from adult mental health services and to liaise with community support and services. It proposes including adults and young people with lived experiences in the interprofessional collaboration. The study data provides initial evidence that the interagency model has added value for youth care professionals who struggle with issues in family-focused care.